A walk along with Jean.Jacques Rousseau An essay - Stanislaus Stefaniak, Andrea (2015)
This article is about analyzing very briefly, using two excerpts of the “Confessions”, the role that walks play in the thought of Jean-Jacques Rousseau (1712-1778), and hence, to share with the students of our institution an epoch-making author in modern European thought. For many authors the experience of a walk is a metaphor for thought, but in Rousseau it occupies a privileged position in the philosophical approach, due to its physical aspect as an existential experience.